Processing of cassava leaves for human consumption - Bokanga, M. (International Society for Horticultural Science, 1994)
In almost all countries of the cassava belt in Africa, from Senegal to Mozambique, cassava leaves are consumed. In much of East Africa, all of Central Africa and parts of West Africa (e.g. Sierra Leone, Liberia), cassava leaves are a major component of the diet and constitute a very significant source of dietary protein, minerals and vitamins. The cyanogenic potential of cassava leaves is 5 to 20 times greater than that of roots. However the risk of intoxication associated with the consumption of cassava leaves is greatly reduced because of the ability of the leaves to rapidly loose cyanogens during processing. The enzyme linamarase which is present in high concentration in cassava leaves is responsible for the removal of cyanogens. Linamarase activity in the leaves is over 200 times greater than in the roots. The removal of cyanogens from cassava roots could be further enhanced if there were greater linamarase activity in cassava roots.